Revisiting collaboration through mixed reality: The evolution of groupware - Ens, Barrett; Lanir, Joel; Tang, Anthony; Bateman, Scott; Lee, Gun; Piumsomboon, Thammathip; Billinghurst, Mark (International journal of human-computer studies, 2019)
•Collaborative MR technology is now mature enough to focus squarely on human needs.•We distil representative literature focusing on collaboration in MR since 1990.•We identify limitations of existing frameworks when applied to collaborative MR.•We identify emerging trends and future directions to support collaboration in MR. Collaborative Mixed Reality (MR) systems are at a critical point in time as they are soon to become more commonplace. However, MR technology has only recently matured to the point where researchers can focus deeply on the nuances of supporting collaboration, rather than needing to focus on creating the enabling technology. In parallel, but largely independently, the field of Computer Supported Cooperative Work (CSCW) has focused on the fundamental concerns that underlie human communication and collaboration over the past 30-plus years. Since MR research is now on the brink of moving into the real world, we reflect on three decades of collaborative MR research and try to reconcile it with existing theory from CSCW, to help position MR researchers to pursue fruitful directions for their work. To do this, we review the history of collaborative MR systems, investigating how the common taxonomies and frameworks in CSCW and MR research can be applied to existing work on collaborative MR systems, exploring where they have fallen behind, and look for new ways to describe current trends. Through identifying emergent trends, we suggest future directions for MR, and also find where CSCW researchers can explore new theory that more fully represents the future of working, playing and being with others.